Survey of Uncontrolled Slaughter in the Central Market of Yakoma City (Nord-Ubangi Province, Democratic Republic of the Congo): The Case of Beefs - Aymard Papy Bembiade; Francis Mosala; Modeste Ndaba Modeawi; Colette Masengo Ashande; Benjamin Zoawe Gbolo; Muhammad Ridwan; Robijaona Rahelivololoniaina Baholy; Koto-Te-Nyiwa Ngbolua (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The danger of uncontrolled slaughter of animals delivered to the market was the subject of a study conducted in the City of Yakoma, in the province of Nord Ubangi in the Democratic Republic of Congo, on its border with the Central African Republic. The aim of this investigation was to provide the population of the city of Yakoma with knowledge on the danger that they are facing due to the negligence of the Veterinary Inspection Service, and to popularize the consequences. Experiments by participatory assistance were carried out on 14 cattle of two different breeds (Zebu and Taurine) for three months with two observations per month. Three samples showed seizure (partial and total), resulting in a prevalence rate of 21.4%. Older cattle had more identification than younger cattle. Several public health contamination hazards are permanent due to the absence of slaughter structures and the unwillingness of the meat inspection service to simply collect taxes instead of controlling the circulation of meat.